Kiai and Blater in Madura’s Local Politics: Islamic Authority and the Limits of Democratization in Post-Reform Bangkalan - Holilah, Holilah; Marijan, Kacung; Mardiyanta, Antun (Postgraduate Studies of UIN Sunan Ampel Surabaya, Indonesia, 2025)
This study explores local politics in Madura, Indonesia, during the early years of regional autonomy following the fall of the New Order, a period marked by the rise of civilian elites in positions previously dominated by the military. It focuses on two influential local actors—kiai (Islamic religious leaders) and blater (local strongmen)—and examines their role in shaping regional elections (Pilkada) in Bangkalan. The research aims to understand community perceptions of these elites’ involvement and its implications for democratization. Adopting a qualitative, descriptive approach, data were collected through interviews and documentation, involving kiai, blater, community leaders, party figures, academics, cultural figures, and residents from both urban and rural areas. The study draws on the theoretical frameworks of interest groups and democratization. Findings indicate that Kiai engage in politics by running for office, endorsing candidates, campaigning, and issuing religious guidance to mobilize followers, while blater employ intimidation and coercion to influence voting behavior. Although both elites are central to local elections, their participation does not advance substantive democracy; instead, it constrains political choice and undermines citizens’ autonomy. The study argues that the entanglement of religious authority and local power structures in Bangkalan illustrates a complex pattern of elite influence, highlighting the challenges of achieving genuine democratization in post-reform Indonesian regions.